Volume 6: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27406
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Stator Well CFD Studies: Effect of Upstream Egress Ingestion

Abstract: There is a constant demand in the turbomachinery industry to improve engine performance, meet stringent environmental and safety regulations, and reduce the time and cost of new product development. As improvements in component efficiencies become increasingly difficult to achieve and new material development has become more expensive over the years, more attention is focusing on other areas of gas turbine technology. Internal cooling air systems, in particular, have been subject to significant research, in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This effect was shown by Gentilhomme et al [9]. The effect of the re-ingestion of cooling air from upstream cavities was investigated by Georgakis et al [10]. It was shown that re-ingestion of upstream egress provided significant contribution to stator well cooling, which was quantified as improving themial effectiveness on the downstream cavity walls.…”
Section: Review Of Flowsmentioning
confidence: 93%
“…This effect was shown by Gentilhomme et al [9]. The effect of the re-ingestion of cooling air from upstream cavities was investigated by Georgakis et al [10]. It was shown that re-ingestion of upstream egress provided significant contribution to stator well cooling, which was quantified as improving themial effectiveness on the downstream cavity walls.…”
Section: Review Of Flowsmentioning
confidence: 93%
“…Georgakis et al [11] computationally investigated re-ingestion into a turbine statorwell, based on the experimental rig at Sussex. They showed that re-ingestion provided GTP-17-1331 Scobie 7 a significant contribution to stator well cooling, calculating an increase in thermal effectiveness of 1 to 1.5% on the cavity walls due to the presence of the upstream egress.…”
Section: Literature Reviewmentioning
confidence: 99%